1918-2018: 100 Years of Theater Research in Iași. International Conference of Doctoral School for Theater and Performing Arts and the Research Center of The Faculty of Theater at the George Enescu National University of Arts - Petcu, Ioana (De Gruyter, 2018)
The Doctoral School for Theatre and Performing Arts and the Research Centre of The Faculty of Theatre at the George Enescu National University of Arts in Iaşi, having the mission of promoting the contribution of personalities in the area of theatre research and creating contexts for sharing their expertise with the doctoral students and young graduates, have proposed holding annual academic meetings. Starting with 2015, these meetings were at first organized as National Symposiums, and, since 2018, they are held as International Conferences. Our purpose is that of rekindling the dialogue between theoreticians and practitioners in our country, at European level and not only.Each year, the participants' contributions were gathered in the pages of consistent volumes that have been indexed on international databases, so that their ideas and information can go further than the context of these meetings. Aims and Scope: - promoting the results of theatre research at national and international level- promoting young researchers- passing the dialogue between theatre theoreticians and practitioners to the wide audience- the continuous discovery of new ways to innovate stage practice, and the revitalization of theoretical resources- creating teams of theatre researchers, professors and doctoral students, theoreticians and theatre practitioners- following the transdisciplinary directions between theatre and connected areas: literature, film, music, philosophy, anthropology, sociology, etc.